2020
DOI: 10.1016/j.dsx.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of structured self-monitoring of blood glucose on glycaemic variability in non-insulin treated type 2 diabetes: The SMBG study, a 12-month randomised controlled trial

Abstract: The impact of structured self-monitoring of blood glucose on glycaemic variability in non-insulin treated type 2 diabetes: the SMBG study, a 12-month randomised controlled trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As previously mentioned, in many studies for patients with non–insulin-treated DMT2, the value of SMBG is inconsistent [ 8 , 11 , 22 - 24 ]. Some studies have demonstrated that SMBG was effective in controlling blood glucose [ 8 , 22 , 23 , 25 ], whereas other studies claimed that SMBG was not effective [ 12 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, in many studies for patients with non–insulin-treated DMT2, the value of SMBG is inconsistent [ 8 , 11 , 22 - 24 ]. Some studies have demonstrated that SMBG was effective in controlling blood glucose [ 8 , 22 , 23 , 25 ], whereas other studies claimed that SMBG was not effective [ 12 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, previous research articles have shown that SMBG is helpful for patients with diabetes mellitus type 1 in controlling blood sugar level. Furthermore, one randomized controlled trial (RCT) recruited patients with diabetes mellitus type 2 (DMT2) and observed them for at least 12 months, and the results suggested that SMBG improves diabetes control [ 11 ]. However, for patients with non–insulin-treated DMT2, the value of SMBG was inconsistent among the studies [ 11 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the benefits are greater when SMBG data are used to adjust the prescription of diabetes medications (-0.3% [-0.4 to 0.1], data from 3 RCTs). The efficacy of structured SMBG was further highlighted by the recent SMBG study in 231 patients with non-insulin-treated T2D, reporting improvements in all measures of glycemic variability with structured monitoring [14].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes management programs have shown to be as or more effective than usual care in providing a significant reduction in hemoglobin A 1c (HbA 1c ) [ 8 - 10 ]. Additionally, structured self-monitoring of blood glucose (SMBG) has been observed to improve glycemic variability and provide greater self-efficacy in management by helping an individual understand lifestyle behaviors’ impact on blood glucose (BG) values over time [ 2 , 11 ]. However, while advances in diabetes treatment options, diabetes management programs, new technologies to support self-management, and the rise in digital health are rushing the market, half of individuals with diabetes have an HbA 1c value of 7.0% or higher and struggle to obtain consistent glycemic control [ 1 ].…”
Section: Introductionmentioning
confidence: 99%